Susceptibilidade a compactação de solos em agroecossistemas no semiárido cearense - Watanabe, Rafaela (2015)
The study of the physical soil conditions and the determination of load bearing capacity in the irrigated areas of the semiarid regions of the Brazilian Northeast are of great practical importance, since it will help with the understanding of the structural, as well as the determination of appropriate use and management practices of soil. The hypotheses of this study are: (i) the compressive behavior of the soil can be used as an indicator of quality management adopted; (ii) the use of systems that accumulate more organic matter in the soil have a lower degree of compaction. The objectives were: (i) determine the preconsolidation pressure, soil compression curve, the least limiting water range and the degree of compaction in soils under different land use systems; (ii) evaluate the relationship between the physical and chemical properties and compressibility of soils under different uses in Ceará semiarid region.